Should we burn the Cerrado? Effects of fire frequency on open savanna plant communities - Rodrigues, Cassy Anne [UNESP]; Fidelis, Alessandra [UNESP] (Wiley, 2022)
Aims: Tropical savanna evolved in the presence of fire, depending on it to maintain its physiognomies and biodiversity. Open ecosystems of tropical savanna burn frequently, and thus changes in fire frequency can affect their plant communities. In this study we aimed to analyze the effects of different fire frequencies on the composition, structure and post-fire regeneration of open savanna plant communities of the Cerrado. Location: Open savannas, Central Brazil (13°35–38′S and 47°45–51′W). Methods: We conducted surveys in areas with different fire frequencies (fire exclusion, burned annually and burned biennially for 6 years, from 2013). Vegetation sampling was carried out before application of fire treatments in 2017, and then 1 and 2 years after. Species cover was estimated visually and later grouped into graminoids, shrubs and forbs. Results: Evaluation of the plant communities after 6 years of fire treatment indicated that fire frequency did not affect species richness. Fire frequency did, however, promote alteration in species occurrence and abundance, resulting in three dissimilar plant communities. Regarding post-fire regeneration, annually burned plots showed consistency in species richness and growth form cover over 6 years of annually applied fire. Biennially burned plots tended to be more variable than the other treatments, with a large increase in species richness and growth form cover in the first year after fire, succeeded by a decrease in the second year. Not all species that were recruited just after fire were able to persist in the above-ground community in the second year after fire. Conclusions: Open savannas of the Cerrado are highly resilient to fire, even to annual fires, with 6 years of annual fire treatments not affecting post-fire species diversity or growth form cover. However, communities differed in species composition, which can influence their functional diversity and lead to alterations in ecosystem services. Our findings encourage long-term studies to evaluate the resilience of areas frequently burned, as well as longer fire exclusion periods.
Keywords: annual fires; communities' dissimilarity; fire exclusion; fire frequency; fire resilience; post-fire regeneration; species richness; woody encroachment